Inglês na escola técnica: perfil dos participantes e proposta de aprendizagem em ambiente virtual - Reis, Susana Cristina dos; Moura, Rafaela Oliveira de (Linguagens & Cidadania, 2017)
This article describes some activities realized in a research project “Language Multimedia Laboratory: contexts, activities and social practices of technical and undergraduate students at a Federal Institute of Science and Technology – Campus Santo Augusto - RS”. Based on a previous analysis of data collected by unstructured questionnaires, we identified the participants’ profile and described a design proposal for a learning virtual space to students to practice the use of foreign languages. The main purpose of elaborating a virtual learning space is to promote language acquisition through virtual interaction with other students by the use of digital technologies, since most of students in this institution have few language background and knowledge, showing high level of difficulties in language learning. As a consequence, we hope that students can practice foreign languages by interacting through the virtual learning space and that pedagogical material can be implemented according to students interest and professional necessity.